On the Role of Urban-to-Rural Remittances in Rural Development - Oded Stark (The Journal of Development Studies, 1980)
In this paper I present a new approach to rural-to-urban migration in developing countries. This approach sheds new light on the role of urban-to-rural remittances in bringing about technological change in the agricultural sector of these countries. At the core of the new approach is a utility maximizing family that by means of the migration of a family member bypasses the constraints on technological change imposed by lack of credit and risk. The paper discusses how to bring the new approach to the data.
Keywords: D1; D7; D13; D15; D19; D81; G11; G23; J43; O12; O13; O15; O33; Q12; Q14; Q16; R23; 330; Rural-to-urban migration; Urban-to-rural remittances; Utility maximizing family; Rural-to-urban remittances; Agricultural development; Technological change in agriculture; Credit constraint; Risk constraint; Credit and insurance markets; Fungibility of urban-to rural remittances; Inequality of the rural income distribution; Usage and interpretation of existing evidence